“Implementación de un módulo didáctico para el análisis de eficiencia mecánica en la turbina pelton en microgeneración hidráulica”. - Lema Neto, Mayra Elizabeth (2023)
This degree work is oriented to obtain the mechanical efficiency of a Pelton turbine since it is currently the most used in micro hydroelectric generation and there is little information focused on its mechanical performance, so it was necessary to implement a didactic module that allows analyzing this performance. The design of the turbine was done in a CAD software, the selected sensors allowed to monitor the physical variables (pressure, flow, torque and angular velocity) that are immersed in the system, where a series of calculations were performed to determine the range of each one of them. The programming was done in the Arduino microcontroller using the Nextion.h, ModbusRtu.h and HX711. h, which allowed to acquire the data to monitor these variables, which were sent by serial communication to the Nextion HMI in which the Performance vs RPM curves were plotted, to determine the maximum and minimum performance of the Pelton turbine was performed in 2 different methodologies (practical and theoretical having a maximum error rate of 3%, where the minimum efficiency was 49% with a drop height of 55 meters, a torque of 2 Nm and the maximum efficiency was 62% with a drop height of 60 meters and a torque of 3.6 Nm.